2005
DOI: 10.1164/rccm.200501-017pp
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress in Pulmonary Fibrosis

Abstract: Idiopathic ulmonary fibrosis (histopathology of usual interstitial pneumonia) is a progressive lung disease of unknown etiology. No treatment has been shown to improve the prognosis of the patients with this disease. Recent evidence, including the observations that the patients with idiopathic pulmonary fibrosis have higher levels of oxidant stress than control patients, and a recent multicenter European study examining the effect of the antioxidant N-acetylcysteine on the progression of idiopathic pulmonary f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
132
1
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 369 publications
(147 citation statements)
references
References 67 publications
2
132
1
1
Order By: Relevance
“…2). Oxidative stress contributes to mouse models of fibrosis, IPF, and other pulmonary diseases (5,(47)(48)(49). We have demonstrated that EC-SOD inhibits syndecan-1 shedding and reduces BALF neutrophil influx in vivo (Fig.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…2). Oxidative stress contributes to mouse models of fibrosis, IPF, and other pulmonary diseases (5,(47)(48)(49). We have demonstrated that EC-SOD inhibits syndecan-1 shedding and reduces BALF neutrophil influx in vivo (Fig.…”
Section: Discussionmentioning
confidence: 82%
“…IPF patients have a mean survival of 3-5 years (1,2) and no effective therapies (3,4), other than orthotopic lung transplantation, have proven to improve survival. The pathogenesis of IPF is poorly understood; however, inflammation and oxidant/antioxidant imbalances in the lung are thought to play important roles (5)(6)(7). A better understanding of the molecular mechanisms involved in oxidative injury and fibrosis could lead to the development of novel therapeutic targets.…”
Section: Idiopathic Pulmonary Fibrosis (Ipf)mentioning
confidence: 99%
“…An important factor in determining the surface and biological reactivity of asbestos fibers is their ability to participate in redox reactions that generate free radicals. Free radicals generated from asbestos fibers and/or damage by fibers are linked to cell signaling, inflammation, and a plethora of other responses associated with the pathogenesis of asbestos-associated diseases (10,(12)(13)(14)(15)(16)(17). The oxidative stress-related nature of asbestos-associated lung injury makes it a good model to study the possible relationship between free radical-induced hyaluronan degradation and the possible protective effects of antioxidants in vivo.…”
mentioning
confidence: 99%
“…12) Reactive oxygen species (ROS) play a crucial role in the development of pulmonary fibrosis induced by BLM. 5) In this study, we observed an increase in MDA content in the lung after BLM injection; however, this increase was attenuated by TJ-19 administration. This result suggests that the preventive effects of TJ-19 on BLM-induced pulmonary fibrosis, at least in part, can be ascribed to antioxidative potential.…”
Section: Discussionmentioning
confidence: 46%